Control of the dynamics and homeostasis of the Drosophila Hedgehog receptor Patched by two C2-WW-HECT-E3 Ubiquitin ligases. Issue 10 (October 2015) - Brigui, Amira; Hofmann, Line; Argüelles, Camilla; Sanial, Matthieu; Holmgren, Robert A.; Plessis, Anne
Abstract : The conserved Hedgehog (HH) signals control animal development, adult stem cell maintenance and oncogenesis. In Drosophila, the HH co-receptor Patched (PTC) controls both HH gradient formation and signalling. PTC is post-translationally downregulated by HH, which promotes its endocytosis and destabilization, but the mechanisms of PTC trafficking and its importance in the control of PTC remain to be understood. PTC interacts with E3 Ubiquitin (UB)-ligases of the C2-WW-HECT family; two of them—SMURF and NEDD4—are known to regulate its levels. We demonstrate that mutation of the PTC PY motif, which mediates binding of C2-WW-HECT family members, inhibits its internalization but not its autonomous and non-autonomous signalling activities. In addition, we show that the two related UB-C2-WW-HECT ligases NEDD4 and SU(DX) regulate PTC trafficking and finely tune its accumulation through partially redundant but distinct functions. While both NEDD4 and SU(DX) promote PTC endocytosis, only SU(DX) is able to induce its lysosomal targeting and degradation. In conclusion, PTC trafficking and homeostasis are tightly regulated by a family of UB-ligases.